Retribusi Masuk Pelabuhan Dengan Sistem Pas Tahunan Di Pt Pelindo II Cabang Bengkulu - Prasetya, Jalu Dwi; Anggraini, Ida (Jurnal Kewirausahaan dan Bisnis, 2024)
The implementation of KKN PT Pelabuhan Indonesia II (Persero) Bengkulu Branch aims to describe efforts to accelerate the achievement of port entry levy withdrawal targets with the annual PAS system which includes: problems, solutions, and actions implemented. The series of activities carried out include; situation analysis, problem formulation, problem priority setting, problem cause analysis, formulation of activities, socialization meetings, making printed socialization media, disseminating information through social media. The outputs produced are; group counseling, printed promotional media in the form of flyers and dissemination of information through social media.